Maintain ecological security: analyzing the impact of the digital economy on green and low-carbon land utilization - Lei, Ting (Frontiers in Environmental Science, 2025)
IntroductionEcological security is an important part of the overall national security outlook. Maintaining ecological security is a fundamental, overall and strategic requirement related to the long-term stability of the country, the sustainable development of the nation and the happiness and well-being of the people. As the fundamental carrier for human survival and development, the utilization mode, intensity and spatial pattern of land directly determine the health, stability and service functions of the ecosystem, and further affect the ecological security of the region and even the world. At present, China’s land resources are confronted with multiple challenges such as ecological and environmental constraints. As a key engine for achieving sustainable utilization of land resources, the digital economy provides a systematic solution for the green and low-carbon use of land. The green and low-carbon utilization of land is an important part of maintaining ecological security. This article explores the promoting effect of the digital economy (DE) on the green and low-carbon utilization of land (GUE). The digital economy is an important way to achieve the carbon reduction targets of land and maintain ecological security.MethodThis paper selects panel data from 31 provinces in China from 2011 to 2023 as research samples, and respectively uses the fixed effects model and the quantile model to explore the promoting and heterogeneous effects of the digital economy (DE) on the green and low-carbon utilization of land (GUE). Furthermore, the mediation model is employed to explore the mediating role of entrepreneurial activity and Internet penetration rate in the digital economy and the green and low-carbon utilization of land, aiming to investigate whether the mediating variables can play a promoting role in maintaining ecological security.ResultFirst, the direct impact of the digital economy and the green and low-carbon utilization of land has shown a significant promoting effect. Second, the entrepreneurial activity level and the Internet penetration rate play a significant mediating role in the assessment of the impact of the digital economy on the green and low-carbon utilization of land. Thirdly, the digital economy has a significant promoting effect on the green and low-carbon utilization of land in the eastern and western regions of China, but it shows no significant effect in the central region.DiscussionThis article not only enriches the theoretical research on the green and low-carbon utilization of land by the digital economy, but also provides corresponding empirical evidence. To provide more precise theoretical support for improving the land governance system and achieving ecological and environmental security. Government departments should enhance policy coordination and institutional allocation for the digital economy, combine the diffusion of green and low-carbon technologies with ecological compensation mechanisms, optimize the allocation efficiency of land factors and green and low-carbon technologies, promote the green and low-carbon transformation and upgrading of land, and while facilitating the realization of land carbon reduction targets, achieve the coordinated evolution of ecological protection and sustainable utilization of land resources. Only by deeply integrating “digitalization” into “greening” can ecological security be achieved under the premise of ensuring the green and low-carbon utilization of land resources, providing a solid foundation for building a moderately prosperous society and creating a modern model of harmonious coexistence between humans and nature.